(untitled) (Fiep Bulletin - online, 2012)
Intrafamiliar violence is considered a public health problem that affects all individuals in the family, including a pregnant woman. The present study aims to analyze the scientific production of nursing and domestic violence involving pregnant women coming together to think about the role of a nurse facing this problem. It is a descriptive qualitative approach through literature search in electronic databases available in SciELO used as descriptors: violence, pregnancy and nursing. Showed the importance of identifying violence during pregnancy as a measure of injury prevention in the health of both mother and child, thus indicating the value of awareness of the professionals involved in health care, especially nurses, since it has more contact with the pregnant woman in the comprehensive care during the prenatal, childbirth and postpartum. In addition, we identified a gap in knowledge production focused on the violence issue / pregnant / nursing. It is necessary to participate in the health sector to implement the support network for women in pregnancy and puerperal process involving multidisciplinary teams that work in an interdisciplinary way able to identify, notify and intervene with pregnant women who are victims of domestic violence, highlighted in this the professional nurse.